(STUDI KEPUSTAKAAN) IMPLEMENTASI ETHNOPARENTING TERHADAP ANAK USIA DINI SUKU BADUY - Halilah, Dinah; Widjayatri, RR. Deni (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This research on the implementation of ethnoparenting has a crucial urgency in the uniqueness that exists in the archipelago. This study raises an interesting issue regarding the upbringing applied by the Baduy culture to children with the customary belief system adopted. Cultural values ​​that are in the area of ​​the Baduy-Lebak Banten tribe have become a hereditary tradition that is realized by parents to children with local customs. The purpose of this study was to determine the application or application of parenting culture in the Baduy tribe. The research method uses a literature study with a qualitative descriptive approach that is studied based on a description of the state of the nature or nature of the value of an object and certain symptoms. The results of the literature study reviewed by researchers describe the parenting applied by Baduy tribal parents implementing local cultural values ​​that have been carried out from generation to generation. This study illustrates that the application of parenting for early childhood in the Baduy Tribe still maintains the ancestral mandate, although the Outer Baduy has begun to adapt to the world of developments, the ancestral mandate is still maintained and preserved. Keywords : Early chilhood, etnoparenting, Baduy tribe